Numerical Simulation Study on Dust Suppression Mechanism of Burning Rock Blasting in Open-Pit Mine - Jia, ZhengZhao; Song, ZiLing; Fan, JunFu; Jiang, JuYu; Guo, ShuPeng (Frontiers in Earth Science, 2022)
In an open-pit mine in Xinjiang, part of the stripped area is covered by burnt rock. Due to the low strength and fragility of burnt rock, dust is more easily generated during blasting. Taking the mining area as the research background, the mechanical property parameters of burnt rock were tested, and the blasting parameter design of on-site operation was understood. The blasting numerical simulation of burnt rock step was carried out by using numerical simulation software (LS-DYNA). From the angle of stress on rock, the stress cloud and stress curve of numerical simulation are analyzed, and it is concluded that the fundamental reason for the large dust production in blasting operation is that the burnt rock is crushed excessively after the action of explosion wave, and the explosive energy is too large, which is converted into kinetic energy to drive the dust to escape. In order to improve the utilization rate of explosives and reduce the output of blasting dust, the original blasting parameters were optimized as 8m hole spacing, 6.5m row spacing, 0.21kg /m³ unit explosive consumption, 1m interval charge and 55ms short-delay blasting through numerical simulation and orthogonal experiment. In the mining area, the measures of dustproof and dust reduction by blasting protection blanket and dust absorption cotton are adopted. Combined with the optimized blasting parameters, the field test proves that the dust removal efficiency is up to 82.4%.